2009
DOI: 10.1111/j.1528-1167.2009.02180.x
|View full text |Cite
|
Sign up to set email alerts
|

Structures involved at the time of temporal lobe spikes revealed by interindividual group analysis of EEG/fMRI data

Abstract: SUMMARYPurpose: We measured metabolic changes associated with temporal lobe (TL) spikes using combined electroencephalography (EEG) and functional magnetic resonance imaging (fMRI). We selected 18 patients with temporal lobe epilepsy (TLE) who underwent a 2-h simultaneous EEG-fMRI and had unilateral or bilateral independent TL spikes for interindividual group analysis, in order to identify consistent blood oxygenation level dependent (BOLD) responses to TL spikes. Methods: EEG was postprocessed and spikes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 25 publications
7
43
2
3
Order By: Relevance
“…Thus, time-consuming patient-specific optimization would be necessary with little potential benefit and reduced BOLD sensitivity in the rest of the brain away from the electrodes. This limitation is relevant since scalp EEG-fMRI studies have shown widespread BOLD signal changes suggestive of distributed epileptogenic networks underlying seemingly focal epileptiform discharges (Federico et al, 2005;Kobayashi et al, 2006Kobayashi et al, , 2009. Because previous studies support the superior BOLD sensitivity at 3 T compared to 1.5 T (Hoenig et al, 2005;Weiskopf et al, 2006), we believe that there would be a greater ability to detect BOLD signals at sites distant from the electrodes.…”
Section: Image Qualitymentioning
confidence: 91%
“…Thus, time-consuming patient-specific optimization would be necessary with little potential benefit and reduced BOLD sensitivity in the rest of the brain away from the electrodes. This limitation is relevant since scalp EEG-fMRI studies have shown widespread BOLD signal changes suggestive of distributed epileptogenic networks underlying seemingly focal epileptiform discharges (Federico et al, 2005;Kobayashi et al, 2006Kobayashi et al, , 2009. Because previous studies support the superior BOLD sensitivity at 3 T compared to 1.5 T (Hoenig et al, 2005;Weiskopf et al, 2006), we believe that there would be a greater ability to detect BOLD signals at sites distant from the electrodes.…”
Section: Image Qualitymentioning
confidence: 91%
“…Largescale physiological brain network function seems to be impaired even in focal epilepsies [7,10,12]. Prominent connections between the striatum and mesiotemporal structures have been known for some time [40].…”
Section: The Bg In Temporal Lobe Epilepsy (Tle)mentioning
confidence: 99%
“…Magnetic resonance imaging, including functional magnetic resonance imaging (fMRI), fMRI-EEG, and spectroscopy [10][11][12][13][14] as well as PET and SPECT data [13][14][15][16][17][18][19] show that the BG play a role in various epileptic syndromes and various types of epileptic seizures.…”
Section: Introductionmentioning
confidence: 99%
“…For example, neuroimaging studies in humans have shown decreased cerebral blood flow (CBF) in frontal and parietal cortex during these events [18,51,59] as well as with interictal discharges [39] causing deactivation in bilateral posterior cingulate during interictal spikes [37].…”
Section: Default Mode Network Involvement In Complex Partial Seizuresmentioning
confidence: 99%